2013
DOI: 10.1021/jp407416h
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding the Photocatalytic Activity of PbMoO4Powders with Predominant (111), (100), (011), and (110) Facets. A Combined Experimental and Theoretical Study

Abstract: A complimentary combination of experimental work and first principle calculations, based on the Density Functional Theory (DFT) method, has been used to increase our limited understanding of the enhanced photocatalytic activity of PbMoO 4 powders with predominant (111), (100), (011), and (110) facets.In this work, PbMoO 4 powders were prepared by the co-precipitation method and processed on a hydrothermal reactor at 100 o C/10 minutes. The variation of different types of modifier such as acetylacetone (acac) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 104 publications
1
51
0
1
Order By: Relevance
“…The (110) and (111) surfaces show that the silver atoms to be surrounded by three oxygen atoms with distances of 1.978, 2.123, and 2.895 Å and 2.077, 2.188, and 2.730 Å, respectively. Surfaces with incompletely coordinated atoms usually have a higher reactivity in photocatalytic processes and diminish more rapidly during crystal growth than surfaces with fully coordinated atoms …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The (110) and (111) surfaces show that the silver atoms to be surrounded by three oxygen atoms with distances of 1.978, 2.123, and 2.895 Å and 2.077, 2.188, and 2.730 Å, respectively. Surfaces with incompletely coordinated atoms usually have a higher reactivity in photocatalytic processes and diminish more rapidly during crystal growth than surfaces with fully coordinated atoms …”
Section: Resultsmentioning
confidence: 99%
“…[1] This finding is intriguing in the senset hat ac ertain particle structure might be thek ey for achieving ah igh photocatalytic activity.T herefore, the morphology, not only the size, but also the shape, and the exposed facets, can be also important and play an important role in photocatalytic efficiency. [2] In this sense, the controllable synthesis of crystal facets of aw ide range of semiconductors, such as TiO 2 , [3] ZnO, [4] Fe 2 O 3 , [5] WO 3 , [6] Ag 3 PO 4 , [7] PbMoO 4 , [8] and a-Ag 2 WO 4 , [9] is becoming an active research field that offers an ew opportunity to further optimize the facet-dependent photocatalytic performance of semiconductor-based photocatalysts. [10] In particular, phosphates have attracted considerable attention from the scientific community owing to their wide range of applications,e specially as photocatalytic materials.…”
Section: Introductionmentioning
confidence: 99%
“…39,[70][71][72][73][74][75][76][77][78] The modifier plays a different role in each type of synthesis, and their effects are not completely understood. The use of a modifier in the chemical synthesis of nanomaterials has been employed to obtain new shapes with different sizes, which promotes the formation of materials with different chemical behaviour.…”
mentioning
confidence: 99%
“…The use of a modifier in the chemical synthesis of nanomaterials has been employed to obtain new shapes with different sizes, which promotes the formation of materials with different chemical behaviour. [76][77][78] According to Lamer and Dinegar, 79 the precursor conversion reactions that limit the crystallization determine the temporal evolution of monomer concentration as well as the steady state supersaturation during the growth phase. In our case, the [Zn(SH) 4 ] 2À complex in solution can be considered as the growth unit for the ZnS nanostructures.…”
mentioning
confidence: 99%
“…Recently, it has been reported that some molybdate compounds exhibit good photocatalytic degradation of organic pollutants. The photocatalytic properties of PbMoO 4 have been recognized for the degradation of various pollutants, such as rhodamine B, orange G, indigo carmine and methyl orange . The photocatalytic performance of CaMoO 4 under UV light irradiation has been reported by Hosseinpour and Sobhani .…”
Section: Introductionmentioning
confidence: 98%